Upaya meningkatkan hasil belajar matematika dengan menerapkan model pembelajaran kooperatif tipe numbered heads together (NHT) di kelas VIII SMP negeri 1 cimahi - Jumriah Jumriah (JUMLAHKU: Jurnal Matematika Ilmiah STKIP Muhammadiyah Kuningan, 2018)
This research is a classroom action research which aims to determine the improvement of student learning outcomes using the Numbered Heads Together (NHT) type of cooperative learning model. This research was conducted in Cimahi 1st Grade VIIIB Public Middle School. The research method used was the classroom action research method, sampling using purposed random sampling. The results of the study found 1, The application of the numbered head together (NHT) method can improve students' mathematics learning outcomes. This can be seen from the increase in average learning outcomes, the average cycle 1 is 64.86, silkus 2 is 69.69 and the cycle 3 is 84 as well as the average grade completeness in cycle 1 is 27.77%, cycle 2 is 53.77% and cycle 3 is 80.56%. While the activities of students in mathematics learning at Cimahi 1 Public Middle School increased continuously, the first cycle was 52.31%, aspects of students' cooperative skills amounted to an average of 60.11%. In the second cycle the aspects of student activity gained an average of 72.68% and aspects of students' cooperative skills were 74.99%. In the third cycle the aspects of student activity averaged 87.03 and aspects of students' cooperative skills averaged 83.79%.